Investigation of Cross-sections for (α, γ) Reactions on p-nuclei 90Zr, 121Sb, 151Eu, and 162Er using Different Models of Radiative Strength Functions - Nhu Le, Nguyen (VNU Journal of Science: Mathematics - Physics, 2023)
In this work, we examine cross sections for ( α, γ ) reactions on p -nuclei, including 90 Zr, 121 Sb, 151 Eu, and 162 Er at astrophysically relevant energies. By using our recently developed α optical model potential ( α -OMP), the ( α, γ ) cross sections were calculated within six models of radiative strength functions (RSF) which consisted of the microscopic HFB-QRPA model based on the BSk-14 Skyrme force, the HF-BCS theory using Skyrme parameters, the EGLO model, SMLO model, the empirical SMLO (SMLOg) and global semi-microscopic (D1M-QRPAg) models. The numerical results is then compared to the measured data of ( α, γ ) cross sections. For the considered ( α, γ ) reactions, the EGLO, SMLO, and HFB results are typically greater than the measured data. In addition, the comparison has indicated that the RSF models of SMLOg and D1M-QRPAg best fit the measured data with rms smaller than 0.2 within our proposed α -OMP. Therefore, for the ( α, γ ) reactions on the selected targets, RSF models of SMLOg and D1M-QRPAg are strongly recommended. The results are significant for a further systematic examination to evaluate which RSF model is most appropriate for studying ( α, γ ) reactions on p -nuclei in general.